High density nonmagnetic cobalt in thin films. (15th March 2018) - Banu, Nasrin; Singh, Surendra; Basu, Saibal; Roy, Anupam; Movva, Hema C P; Lauter, V; Satpati, B; Dev, B N
Abstract: Recently high density (HD) nonmagnetic cobalt has been discovered in a nanoscale cobalt thin film, grown on Si(111) single crystal. This form of cobalt is not only nonmagnetic but also superconducting. These promising results have encouraged further investigations of the growth of the nonmagnetic (NM) phase of cobalt. In the original investigation, the cobalt film had a natural cobalt oxide at the top. We have investigated whether the growth of HD NM cobalt layers in the thin film depends on (i) a capping layer on the cobalt film, (ii) the thickness of the cobalt film and (iii) the nature of the substrate on which the cobalt film is grown. The results of such investigations indicate that for cobalt films capped with a thin gold layer, and for various film thicknesses, HD NM cobalt layers are formed. However, instead of a Si substrate, when the cobalt films are grown on oxide substrates, such as silicon oxide or cobalt oxide, HD NM cobalt layers are not formed. The difference is attributed to the nature—crystalline or amorphous—of the substrate.